Search for a new resonance decaying to a W or Z boson and a Higgs boson in the ℓℓ/ℓν/νν+bb[bar] final states with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Hanke, Paul; Jongmanns, Jan; Kluge, Eike-Erik; Kugel, Andreas; et al. (The European physical journal. C, Particles and fields, 2015)
A search for a new resonance decaying to a W or Z boson and a Higgs boson in the ℓℓ/ℓν/νν+bb¯ final states is performed using 20.3 fb−1 of pp collision data recorded at s√= 8 TeV with the ATLAS detector at the Large Hadron Collider. The search is conducted by examining the WH / ZH invariant mass distribution for a localized excess. No significant deviation from the Standard Model background prediction is observed. The results are interpreted in terms of constraints on the Minimal Walking Technicolor model and on a simplified approach based on a phenomenological Lagrangian of Heavy Vector Triplets.